Morphological changes in hooded crows (Corvus cornix) related to urbanization - Benmazouz, Isma; Jokimäki, Jukka; Juhász, Lajos; Kaisanlahti-Jokimäki, Marja-Liisa; Paládi, Petra; Kardos, Gábor; Lengyel, Szabolcs; Kövér, László (Frontiers in Ecology and Evolution, 2023)
Urbanization has led to a recent surge of interest in urban biodiversity, and wildlife responses to urban environments have become a hot topic in environmental sciences and biodiversity conservation. However, adaptations to urbanization and the factors driving them are less understood. We studied possible morphological adaptations to urban environments by comparing body size and condition of adult and post-fledging juvenile Hooded Crows (Corvus cornix), a bird species that has recently colonised cities in eastern Europe, between two urban and two rural populations, between two different-sized cities and between locations within one city in Hungary. Adult crows from the rural cropland-woodland area were lighter and in poorer condition than crows from the rural grassland area or those from the medium-sized city. There were no differences in morphological traits of adults or juveniles between the large and the medium-sized cities. The comparison of multiple trapping locations within the city of Debrecen showed that juveniles in the Zoo area were larger, heavier, and in better condition than individuals in the other locations and that adults in the Zoo had longer wings and tarsi than adults in other locations. Our results indicated that urbanized Hooded Crows showed some morphological changes to live in urban environments, but we did not find large-scale, consistent differences between urban and rural areas. However, we found significant variation within one city. Our results suggest that urban-rural environmental differences may be mediated by local factors, of which the year-round availability of anthropogenic food is fundamental. Such food is widely available in cities, although its quality may be suboptimal for bird development.Our study suggests that the variation in body size variables is probably more site-dependent than gradient-dependent and shows that documenting wildlife adaptations to urban environments requires multiple spatial scales ranging from regional to local (within-city) scales.